2017
DOI: 10.17221/606/2017-pse
|View full text |Cite
|
Sign up to set email alerts
|

The contents of free amino acids and elements in As-hyperaccumulator Pteris cretica and non-hyperaccumulator Pteris straminea during reversible senescence

Abstract: Several species of the genus Pteris including P. vittata and P. cretica (PC) have been identified as arsenic hyperaccumulators (Luongo and Ma 2005). On the other hand, Meharg (2003) first reported P. straminea (PS) as a non-hyperaccumulator plant. The phytochelatins play a key role in As (arsenic) detoxification in non-hyperaccumulators (Raab et al. 2004). In contrast to non-hyperaccumulators, hyperaccumulators complex only 1-3% As with phytochelatins (Zhao et al. 2003, Vetterlein et al. 2009), because As deto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…in the drop of photosynthetic performance under As(V) toxicity is attributed to a decrease in maximal rate of RuBisCO carboxylation, which is reversed by nitrogen availability. Arsenic toxicity was found to be compensated primarily by upregulation of photosynthetic parameters and key nitrogen metabolizing enzymes [36]. In this experiment with Solanum lycopersicum L., major photosynthetic criteria like net photosynthetic rate and maximum quantum efficiency of photosystem II were significantly reduced under As(V) stress.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…in the drop of photosynthetic performance under As(V) toxicity is attributed to a decrease in maximal rate of RuBisCO carboxylation, which is reversed by nitrogen availability. Arsenic toxicity was found to be compensated primarily by upregulation of photosynthetic parameters and key nitrogen metabolizing enzymes [36]. In this experiment with Solanum lycopersicum L., major photosynthetic criteria like net photosynthetic rate and maximum quantum efficiency of photosystem II were significantly reduced under As(V) stress.…”
Section: Introductionmentioning
confidence: 73%
“…Our previous results show that N flow via amino acids can change dramatically in response to stress caused by toxic elements [35][36][37]. Pityrogramma calomelanos tolerates high concentrations of As due to its ability to upregulate the biosynthesis of amino acids and antioxidants, without greatly disturbing central carbon metabolism [33].…”
Section: Introductionmentioning
confidence: 99%
“…SAR was detected only in the leaves of the Multi variant. Pavlíková et al [90] observed that SAR and HYP were not detected in the As hyperaccumulator Pteris cretica or the non-hyperaccumulator P. straminea. However, SAR content was confirmed in hyperaccumulators of Noccaea species [83], and the authors assumed that SAR could form complexes with Cd and other metals and protect nucleic acids from oxidative stress [91].…”
Section: Response Of Free Amino Acids To CD Pb and Znmentioning
confidence: 99%